Highs and lows: a behavioral and technical analysis - Bruce Mizrach; Susan Zhang Weerts (Rutgers University, Department of Economics, 2007)
We find that turnover rises on n-day highs and lows and is an increasing function of n. We offer several explanations from the technical and behavioral finance literature for why traders might use these signals. Turnover is persistent following these events, and new lows provide abnormal returns for up to 6 trading days.
Keywords: G14; G20; 330; Abnormal returns; behavioral finance; n-day high/low; technical analysis; turnover